La gestión del conocimiento, como herramienta gerencial para crear competitividad en las organizaciones (2020)
The work presented below has as an end, due research and documentation on the topic "Knowledge Management, as a managerial tool to generate Competitiveness in Organizations", performing the due analysis of books and articles, obtained from databases available at the University of America Foundation. This research paper focuses on how tacit and implicit knowledge is the basis, for the creation of a Knowledge Management Plan, to achieve the creation of a competitive advantage, making use of each of the areas owned by the company to be in constant generation of knowledge and innovation.